Islamic Boarding School Education and Its Renewal According to K.H. Abdullah Syukri Zarkasyi - Muhammad Thoriqul Islam; Imam Qodari; Nawa Marjany (PAEDAGOGIA, 2024)
Education is currently faced with problems of crime and deviant behavior, which hinder the effectiveness of teaching Islamic teachings. Effective educational management and experienced leaders are required. One solution is to implement an integrated curriculum as proposed by KH. Abdullah Syukri Zarkasyi in reforming Islamic boarding school education. This research aims to understand the concept of Islamic boarding school education and its renewal according to KH. Abdullah Syukri Zarkasyi. This type of research is qualitative, using the literature review method by obtaining data through journals, books, and documentaries and comparing, contrasting, and critiquing data using thematic analysis techniques. The research results show that according to K.H Abdullah Syukri Zarkasyi, good Islamic boarding school education is based on the values of the five souls of Islamic boarding schools and is total. The reform of Islamic boarding school education that he proposed was rooted in the concept of the five souls of Pondok Modern Darussalam Gontor. K.H. Abdullah Syukri Zarkasyi emphasized three fundamental things in this reform: the totality of life in education, integral education, and Islamic boarding school education orientation.